Ecosystem respiration, methane and nitrous oxide fluxes from ecotopes in a rewetted extracted peatland in Sweden - S. Jordan; M. Strömgren; J. Fiedler; L. Lundin; E. Lode; T. Nilsson (Mires and Peat, 2016)
Ecosystem respiration (carbon dioxide; CO2), methane (CH4) and nitrous oxide (N2O) fluxes to the atmosphere were determined using an opaque closed chamber method within various ecotopes (vegetation covered, bare peat and open water) in a rewetted extracted peatland and within an adjacent open poor fen in Sweden. Ecotopes had a significant impact on CO2 and CH4 fluxes to the atmosphere. Ecosystem respiration and CH4 emissions from the bare peat site, the constructed shallow lake and the open poor fen were low but were much higher from ecotopes with Eriophorum vaginatum tussocks and Eriophorum angustifolium. A combination of vascular plant cover and high soil temperatures enhanced ecosystem respiration, while a combination of vascular plant cover, high water table levels and high soil temperatures enhanced CH4 emissions. N2O emissions contributed little to total greenhouse gas (GHG) fluxes from the soil-plant-water systems to the atmosphere. However, the overall climate impact of CH4 emissions from the study area did not exceed the impact of soil and plant respiration. With regard to management of extracted peatlands, the construction of a nutrient-poor shallow lake showed great potential for lowering GHG fluxes to the atmosphere.